Physical Activity in Different Preschool Settings: An Exploratory Study - Röttger, Katrin (Hindawi Publishing Corporation, 2014)
Introduction. Physical activity (PA) in preschoolers is vital to protect against obesity but is influenced by different early-life factors. The present study investigated the impact of different preschool programs and selected family factors on preschoolers' PA in different countries in an explorative way. Methods. The PA of 114 children (age = 5.3 ± 0.65 years) attending different preschool settings in four cities of the trinational Upper Rhine region (Freiburg, Landau/Germany, Basel/Switzerland, and Strasbourg/France) was measured by direct accelerometry. Anthropometrical and family-related data were obtained. Timetables of preschools were analyzed. Results. Comparing the preschool settings, children from Strasbourg and Landau were significantly more passive than children from Basel and Freiburg (P < .01). With regard to the family context as an important early-life factor, a higher number of children in a family along with the mother's and child's anthropometrical status are predictors of engagement in PA. Conclusion. More open preschool systems such as those in Basel, Freiburg, and Landau do not lead to more PA “per se” compared to the highly regimented desk-based system in France. Preliminaries such as special training and the number of caregivers might be necessary elements to enhance PA. In family contexts, targeted PA interventions for special groups should be more focused in the future.